The Dangerous Allure of Trends: The Influence of Fear of Missing Out on Brand Passion and Its Effect on Compulsive Buying of Fashion Products in Indonesia - Ezra Aulia Najwa Dewi; Alldila Nadhira Ayu Setyaning (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data collected from 305 respondents. The purpose of the research is to examine the influence of fear of missing out (FoMO) on harmonious brand passion and obsessive brand passion, as well as its impact on compulsive purchasing behaviors, including impulsive buying and obsessive-compulsive buying in the context of fashion consumption in Indonesia. The results show that FoMO has a positive and significant effect on both forms of brand passion. Additionally, both harmonious brand passion and obsessive brand passion positively and significantly influence impulsive buying. These two types of brand passion also contribute to higher levels of obsessive-compulsive buying. The findings highlight that FoMO and brand passion play substantial roles in shaping unplanned and repetitive purchasing behaviors among fashion consumers, underscoring the importance for marketers to understand these psychological dynamics when developing marketing strategies.